Romania : Ex Post Evaluation of Exceptional Access Under the 2009 Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2012)
This paper discusses ex-post evaluation of Romania's exceptional access under the 2009 Stand-By Arrangement. Concerns about Romania's external and fiscal sustainability have triggered significant increase in external borrowing costs as sovereign yields jumped to 9 percent. Banks also came under increasing pressure, with liquidity drying up from the interbank market. Rollover risks also increased as the maturity structure gradually deteriorated, and reserves coverage of shorter-term external debt declined. The large and front-loaded financing along with upfront fiscal actions has helped quickly to restore market confidence, with a successful return to private financial markets during the program period.